Strategi Peningkatan Cakupan dan Akurasi Data Akta Kelahiran Usia Produktif dalam Implementasi Administrasi Kependudukan - Ledi Erlina; Ria Ariany; Sabri; Rahmad (FKDP (Forum Komunikasi Dosen Peneliti), 2026)
This study aims to analyze the implementation of population administration policies in issuing birth certificates for the productive age group in Payakumbuh City, examine ownership coverage, assess data accuracy, and formulate strategies for improvement. The main issue is the low coverage of birth certificate ownership among the productive age group, which only reaches 47.19%, far below the coverage of children aged 0–18 years at 99.53% and the overall coverage of 58.05%. Data accuracy also remains problematic, as indicated by 58 corrections out of 4,233 certificates issued in 2025. This research employs a qualitative approach using interviews, observations, and documentation, with data analysis based on Miles and Huberman’s model and validation through source and technique triangulation. Policy implementation is analyzed using George C. Edward III’s framework of communication, resources, disposition, and bureaucratic structure. Findings reveal that communication and outreach are not yet optimal, public awareness is low, and data accuracy is not fully guaranteed. Strategies proposed include updating population data, integrated services, document verification, and proactive outreach to the productive age group. These efforts are expected to enhance both coverage and accuracy of birth certificate ownership sustainably.